Returning to more finished genomes - Jonas Korlach (Genomics Data, 2014)
Genomic data have become commonplace in most branches of the biological sciences and have fundamentally altered the way research is conducted. However, the predominance of short-read sequence data from second-generation sequencing technologies has commonly resulted in fragmented and partial genomic data characteristics. In this opinion, I will highlight how long, unbiased reads from single molecule, real-time (SMRT) sequencing now allow for a return to more contiguous and comprehensive views of genomes.